EFEK SITOTOKSIK HAARLEM OIL TERHADAP HL-60 CELL LINE DAN Steinernema feltiae (Cytotoxic Effect of Haarlem Oil on HL-60 Cell Line and Steinernema feltiae) - Bahi, Muhammad; Jacob, Claus; Khairan, Khairan (Universitas Syiah Kuala, 2016)
The objective of this research was to investigate cytotoxicity effect of Haarlem oil (HO) on HL-60 cell line and Steinernema feltiae (S. feltiae). The test results using trypan blue method and CellTiter-Glo assays revealed that HO showed higher cytotoxicity effect against HL-60 cell line especially at concentration of 1:10 and 1:5. Meanwhile, the MTT (3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay revealed that the higher cytotoxicity effect showed at 1:5, with the cell viabilities were around 40-65%. The nematicidal assay discovered that HO at concentration of 1:5 showed higher activities compare to other concentrations with percentage viability of 70%. These studies have shown that HO shows cytotoxic effect against HL-60 cell lines, and moderate activity against S. feltiae as well.